TRANSFORMASI NALAR BAHTSUL MASAIL DALAM KEPUTUSAN REGULASI MINUMAN BERALKOHOL OLEH LBM PWNU DIY - Muhammad Rifqi (Universitas Nahdlatul Ulama Surakarta, 2025)
The adverse effects of alcoholic beverages have increased crime rates in Indonesia. As a preventive measure, the government has issued a policy regulating the distribution of alcoholic beverages. However, this policy is considered problematic and has sparked controversy from various parties, including religious institutions. This article explores the views of the Bahtsul Masail Institute (LBM) PWNU DIY on the regulation of alcoholic beverages in Indonesia. Specifically, it examines the arguments that form the basis for supporting this regulation. This study uses a qualitative approach with a literature review and descriptive-analytical presentation. The primary source is taken from the bahtsul masail decision of LBM PWNU DIY on November 9, 2024, which took place at the ORA AJI Islamic Boarding School in Sleman. Meanwhile, secondary sources are taken from news, articles, and other relevant supporting scientific works. The findings of this study show that there are three main arguments that emerge: First, the use of maqashid al-syariah. Second, consideration of the social and economic situation. Third, legal compromise. These three findings form the basis for the LBM PWNU DIY in supporting the government's policy on the restriction of alcoholic beverages. The findings also show a shift in the reasoning of bahtsul masail in the process of exploring fiqh law from the concept of “qauli” (following the views of classical scholars) which is theocentric to “manhaji” (using a contextual methodological framework) which considers actual human needs.